Respostas
respondido por:
1
y= f(x)
função y= 5x+6 = f(x)= 5x+6
então
f(-3)= 5.(-3)+6
f(-3)= -15+6
f(-3)=-9
f(0)= 5.0+6
f(0)= 0+6
f(0)= 6
f(4)= 5.4+6
f(4)= 20+6
f(4)= 26
f(6)= 5.6+6
f(6)= 30+6
f(6)= 36
função y= 5x+6 = f(x)= 5x+6
então
f(-3)= 5.(-3)+6
f(-3)= -15+6
f(-3)=-9
f(0)= 5.0+6
f(0)= 0+6
f(0)= 6
f(4)= 5.4+6
f(4)= 20+6
f(4)= 26
f(6)= 5.6+6
f(6)= 30+6
f(6)= 36
nandynha26:
muito obrigada ❤
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás